2017
DOI: 10.1007/978-3-319-58068-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Source-Object Networks to Resolve Object Conflicts in Linked Data

Abstract: Considerable effort has been exerted to increase the scale of Linked Data. However, an inevitable problem arises when dealing with data integration from multiple sources. Various sources often provide conflicting objects for a certain predicate of the same real-world entity, thereby causing the so-called object conflict problem. At present, object conflict problem has not received sufficient attention in the Linked Data community. Thus, in this paper, we firstly formalize the object conflict resolution as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…We selected three popular RDF data fusion systems for comparative experiments. They are ObResolution [2], Truth Discovery [11], MINTE [12]. Our method is called RDFSim+KNN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected three popular RDF data fusion systems for comparative experiments. They are ObResolution [2], Truth Discovery [11], MINTE [12]. Our method is called RDFSim+KNN.…”
Section: Resultsmentioning
confidence: 99%
“…Our task is to map the already formed images in IM Data fusion is carried out to form a complete and brief centralized data set. We from IM@OAEI (2010) 1 and IM@OAEI(2019) 2 has built two data sets with two types: restaurant and creative work. Each type of data has two heterogeneous data sets, and our task is to fuse the two data sets in each type.…”
Section: Real Rdf Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effectiveness of existing truth discovery methods is significantly affected by the number of objects provided by each source. In our previous work [5], we found that the number of conflicting objects provided by most of the sources ranges from 1 to 10, and only a few sources have many conflicting objects. This finding indicates that Linked Data has a scale-free property.…”
Section: Introductionmentioning
confidence: 96%
“…Section 5 presents the conclusions of this demonstration. Source Belief Graph [5]: Given a SameAs Graph SG, the Source Belief Graph can be denoted by SBG = (W, R), where W is a set of vertices with each vertex corresponding to the source name of the vertex in SameAs Graph SG; R is a multiset of W × W formed by pairs of vertices (µ, ν), µ, ν ∈ W and each pair (µ, ν) corresponds to an edge in SameAs Graph SG.…”
Section: Introductionmentioning
confidence: 99%